A study on the determinants of job stress among employees in Harta Maintenance Sdn Bhd / Siti Norliana Hamdan - Hamdan, Siti Norliana (2013)
The workplace has changed dramatically due to globalization of the economy, use of new information and communications technology, and growing diversity in the workplace. The increased complexity and the imperative of global competition have exerted tremendous pressure on workers and thus imposed considerable stress on them. Thus, job stress becomes a common problem faced by employees in many organizations today. It affects employee’s mental and physical health and in the long run affects company’s performance. The main purpose of this study was to investigate the relationship of job stress, leadership style, individual, and working environment at Harta Maintenance Sdn Bhd. Leadership style, individual and working environment were used to predict the determinants of job stress among employees at Harta Maintenance Sdn Bhd. In this study, a survey has been conducted with the help of questionnaire in which a likert-scale question has been used. Findings showed that leadership style, individual and working environment has significant relationship with job stress. It shows that leadership style, individual and working environment are the determinants of job stress among employees at Harta Maintenance Sdn Bhd.